Peningkatan kemampuan literasi informasi melalui pelatihan literasi informasi: Sistematik review - Mahardhini, Orisa; ,, Rahmi; Rahmawati, Nur Sanny (LIBRARIA : Jurnal Ilmu Perpustakaan dan Informasi, 2021)
Information literacy is an essential ability that a person needs to sort information amid the flow of information development. Information literacy is a set of capabilities that help identify data and are valuable for consideration and decision making. This study aims to complete the previous research gap by examining the formulation of strategies, efforts, and implementation of improving information literacy skills through training. The method used in this study is a systematic literature review with details of the identification of research questions and limitations, strategies and determination of search terms, and selection of criteria to assess the quality of research. Based on the findings of scientific papers in this study, 2017 and 2018 were the years of publication of the most information literacy scientific works, namely 3 (three) scientific works. Furthermore, the most widely used information literacy model in research is The Big6 model; there are 5 (five) articles where the majority discuss several things regarding its implementation, including helping in identifying the information needed, helping in selecting and comparing relevant information. To discussions, introducing the Online Public Access Catalog, helping teach information literacy related to naming information sources, and assisting in finding information and evaluating information and resources critically. Challenges in improving information literacy skills include ICT, information explosion, and information literacy skills. Keywords: Information Literacy, Systematic Literature Review, Information Literacy Model